Sustainable swimwear in Portugal : perceptions and purchase intentions - Girão, Teresa Limpo de Lacerda Pestana (2020)
Sustainable products are a rising trend in Portugal since concerns about the environment have been increasing over the last years. The fashion industry did not let the opportunity escape, and over this year, the appearance of sustainable swimwear made of recycled or upcycled materials has boosted. Hence, the present dissertation aims to explore the Portuguese females’ perceptions and purchase intentions towards sustainable swimwear products. Thus, three research questions were answered: (1) Who is the consumer, (2) What are the main drivers that lead to intentions of purchase, and (3) What are the main barriers that prevent consumers from purchasing the product. For this purpose, past literature was reviewed, and two methodologies were conducted: eight in-depth interviews and an online survey (418 participants). Results indicated that the Portuguese female consumer is a young adult, with high levels of education and with a monthly income between 1001€-1500€. Under a comparative analysis, the main drivers of purchase intentions found were knowledge about the environment, sustainable lifestyle, and psychographic factors. Lastly, the main barriers to the purchase were lack of information about the product, hard purchase access, and price.